2020
DOI: 10.4236/cn.2020.123006
|View full text |Cite
|
Sign up to set email alerts
|

A P2P Approach to Routing in Hierarchical MANETs

Abstract: We present an effective routing solution for the backbone of hierarchical MANETs. Our solution leverages the storage and retrieval mechanisms of a Distributed Hash Table (DHT) common to many (structured) P2P overlays. The DHT provides routing information in a decentralized fashion, while supporting different forms of node and network mobility. We split a flat network into clusters, each having a gateway who participates in a DHT overlay. These gateways interconnect the clusters in a backbone network. Two routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…The peer-to-peer systems and especially the DHTs, such as [9,11,12,33] have been introduced for quite some time, and have been the starting point for data sharing in distributed filesystems [1,19], but also for file sharing in home networks [43,44] or even in early IP telephony solutions [45]. Very recently, the DHTs have come into focus again, in storage and replication [6], in name resolution and resource lookup [2,3,13], but also in routing [15], and even in blockchain [2,3] design. Nevertheless, despite their very good quality to balance loads, a feature which derives from the properties of the hash function, the authors have not identified DHTs and peer-to-peer networks to be used in order to simplify and make more available services of data processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peer-to-peer systems and especially the DHTs, such as [9,11,12,33] have been introduced for quite some time, and have been the starting point for data sharing in distributed filesystems [1,19], but also for file sharing in home networks [43,44] or even in early IP telephony solutions [45]. Very recently, the DHTs have come into focus again, in storage and replication [6], in name resolution and resource lookup [2,3,13], but also in routing [15], and even in blockchain [2,3] design. Nevertheless, despite their very good quality to balance loads, a feature which derives from the properties of the hash function, the authors have not identified DHTs and peer-to-peer networks to be used in order to simplify and make more available services of data processing.…”
Section: Discussionmentioning
confidence: 99%
“…The most representative model for decentralization is the peer-to-peer model [9][10][11][12], which has evolved in recent years and is currently also applied for name lookup [3,13] and for in-fashion Blockchain solutions [2,3,14], but peer-to-peer networks are also used in highly decentralized and unstructured overlay networks, such as in [15]. The peerto-peer architecture is decentralized and offers a higher flexibility and a better tolerance to individual components and node failures.…”
Section: Introductionmentioning
confidence: 99%
“…Nodes use specific hashing methods to hash metadata such as IP addresses and obtain ID values and other identifiers. And it can be mapped to a point on the ring based on the ID value [9][10][11]. The schematic diagram of node movement is shown in Figure 1.…”
Section: Distributed Hash Table Load Balancing Designmentioning
confidence: 99%
“…There exist no explicit and direct solutions to the problem. To the best of author's knowledge, existing DHT-based routing protocols in MANETs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] mainly consider routing and resilience of the address spaces used. In other words, existing protocols do not consider network dynamics and associated issues that limit the scope of these protocols in the adversarial environment of MANET.…”
Section: Imentioning
confidence: 99%
“…DHT provides a scalable way to decouple node location from its identity and facilitate general mapping between them. In the last few years, several DHT-based routing protocols for MANETs have been proposed that eliminate flooding in the route discovery, thus making the network more scalable [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In DHT-based routing protocols, a node is assigned a logical identifier (LID) in addition to its permanent identifier (i.e., MAC/IP address also known as user id, i.e., UID) based on the LIDs of its physical neighbors.…”
Section: Introductionmentioning
confidence: 99%